The individualisation of glycaemic targets in response to patient characteristics in type 2 diabetes: a scoping review. Issue 3 (2022) - Westall, Samuel J; Narayanan, Ram Prakash; Watmough, Simon; Irving, Greg; Furlong, Niall
No abstract available